PENGARUH UNDANG-UNDANG CIPTA KERJA DALAM MENGATASI PENGANGGURAN DI INDONESIA - Krista Yitawati (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
This research aims to determine the influence of the Job Creation Law in overcoming unemployment in Indonesia, namely. This research is normative research using conceptual studies (conceptual approach) and statutory studies (statute approach). The Job Creation Law was formulated to realize the goal of establishing the Indonesian Government and realizing a prosperous, just and prosperous Indonesian society based on Pancasila and the 1945 Constitution. The State needs to make various efforts to fulfill citizens' rights to work and a decent living for humanity through create work. Job creation is expected to be able to absorb as wide a workforce as possible in Indonesia amidst increasingly competitive competition and the demands of economic globalization as well as global economic challenges and crises which can cause disruption to the national economy.